2020
DOI: 10.21203/rs.3.rs-53254/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The New Zealand Podiatry profession – a workforce in crisis?

Abstract: Background This is the first study to explore workforce data from the Podiatrists Board of New Zealand. The study analysed data from an online survey which New Zealand podiatrists complete as part of their application for an Annual Practising Certificate.Methods Survey responses between 2015 and 2019 were analysed. Data was related to work setting, employment status, work hours, location, professional affiliations, and number of graduates entering practice. Survey data was downloaded by a second party who pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Most (82 %) worked in private practice and were either employed (37 %) or selfemployed (57 %). These demographics are consistent with 2019 national data obtained by Carroll and colleagues [31], which reported that the New Zealand podiatry profession is mainly female (67 %), work in private practice (80 %), and are self-employed business owners (69 %) or employees (37 %).…”
Section: Podiatrist Demographicssupporting
confidence: 89%
“…Most (82 %) worked in private practice and were either employed (37 %) or selfemployed (57 %). These demographics are consistent with 2019 national data obtained by Carroll and colleagues [31], which reported that the New Zealand podiatry profession is mainly female (67 %), work in private practice (80 %), and are self-employed business owners (69 %) or employees (37 %).…”
Section: Podiatrist Demographicssupporting
confidence: 89%